Charter and Ordinances of the City of Macon 38 (1853) - (:unkn) unknown (My University, 1853)
§ 5: Prohibited the discharge of a gun, pistol, or any other fire-arms within three hundred yards of any house. Also prohibited burning rockets, crackers, or any kind of fireworks within the limits of the city. Violators fined not exceeding twenty dollars.
Keywords: DISCHARGE